Innovative Socio-Economic Policy for Improving Environmental Performance - United Nations Economic; Social Commission for Asia; the Pacific (United Nations, 2016)
The conventional “grow first, clean up later” approaches to economic growth are increasingly placing the futures of regional economies and societies at risk. The forward-thinking policymaker is tasked to promote development based on eco-efficient economic growth and at the same time, record more inclusive gains in human welfare and socio-economic progress. In order to assist policymakers in responding to such challenges, ESCAP’s “Greening of economic growth” series provides quick access to easy-to-read guidance to specific policy tools.